2006
DOI: 10.1093/rheumatology/kel210
|View full text |Cite
|
Sign up to set email alerts
|

p21 gene polymorphisms in systemic lupus erythematosus

Abstract: Our results suggested that the p21US A allele and p21-1022 A allele were both associated with the development of SLE, and the p21US A allele was associated with arthritis in SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…However, because the -2266G [ A polymorphism is located in the vicinity of the p53 binding site, the -2266 G-to-A change might increase the binding affinity of p53, and, thus, enhance P21 expression. This explanation is in agreement with the previous report (Kong et al 2007), in which individuals carrying the -2266 GA or AA genotype had higher p21 mRNA expression than carriers with the -2266 GG genotype. Another possible explanation is that the observed effect of the -2266G [ A polymorphism on the risk of lung cancer may be secondary to LD with other functional P21 variants.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, because the -2266G [ A polymorphism is located in the vicinity of the p53 binding site, the -2266 G-to-A change might increase the binding affinity of p53, and, thus, enhance P21 expression. This explanation is in agreement with the previous report (Kong et al 2007), in which individuals carrying the -2266 GA or AA genotype had higher p21 mRNA expression than carriers with the -2266 GG genotype. Another possible explanation is that the observed effect of the -2266G [ A polymorphism on the risk of lung cancer may be secondary to LD with other functional P21 variants.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, most studies have focused on the S31R (C98A in exon 2, rs1801270) polymorphism. Recently, it has been demonstrated that -2266G [ A (rs4135234), at 5 bp upstream from the p53 binding site, and -1022G [ A (rs762623), in the putative binding site of the E2F transcription factor, both increase p21 expression (Kong et al 2007). Therefore, a case-control study in a Korean population was performed to further verify the role of P21 polymorphisms on the risk of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is noteworthy that the CDKN1A gene is located on chromosome 6 in relative proximity to MHC class I genes, some of which are significantly associated with the elite controller phenotype (10,30). Although we did not observe any relationship between p21 expression intensity in CD4 + T cells and protective HLA alleles, such as HLA-B57 and HLA-B27, it remains to be determined in larger studies whether MHC class I gene polymorphisms associated with better HIV-1 disease outcomes are linked to specific mutations in the CDKN1A gene (31,32) that may affect its expression. Moreover, the transcription factor Foxo3A, which may be involved in the regulation of CDKN1A gene expression, is uniquely expressed in CD4 + T cells from elite controllers (33), and it will be important to analyze whether it participates in the epigenetic control of high-level p21 expression in such cells.…”
Section: Discussionmentioning
confidence: 76%
“…This allelic heterogeneity may result from the differences in allele frequency, linkage disequilibrium structure or causal variants among different ethnic populations. For example, the minor allele frequency of rs762623 in control subjects appears to vary markedly among different populations, specifically, 6.7% in Hong Kong Chinese, 20 7.5% in sub-Saharan Africans (HapMap YRI), 11.1% in Han Chinese (HapMap HCB), 12.2% in Koreans (this study), 13.3% in European Caucasians (HapMap CEU) and 21.1% in Japanese (HapMap JPT). Furthermore, SNPs in the CDKN1A promoter region do not appear to be tightly linked to each other in several ethnic populations (r 2 p0.33 in Koreans).…”
mentioning
confidence: 62%
“…Kong et al 20 showed an association of two SNPs (rs4135234 and rs762623) in the CDKN1A promoter with SLE susceptibility in a Hong Kong Chinese population. One of these two SNPs, rs762623, was not associated with SLE susceptibility in Koreans (Table 1).…”
mentioning
confidence: 99%